Development of Statistical Teaching Materials using Statcal to Enhance Students' Statistical Literacy and Self-Efficacy - Elfitra Elfitra; Tiur Malasari Siregar; Suci Frisnoiry (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study addresses the challenges of limited teaching materials and the need for innovative tools to enhance students' statistical literacy and self-efficacy by developing inferential statistics teaching materials integrated with Statcal software. The primary aim is to create and evaluate the effectiveness of these materials in improving students' skills and confidence in statistical learning. Methodology: The research employed a qualitative approach and involved collaboration with two material expert lecturers, one statistical program expert lecturer, and one student. The development process followed four stages: definition, design, development, and dissemination, ensuring a comprehensive framework for creating effective teaching resources Main Findings: Validation results showed the materials were valid with a score of 4.21, practical with an 83.72% score, and effective with an 82.4% score, all in the good category. Additionally, the teaching materials significantly improved students' statistical literacy (72.78%) and self-efficacy (73.52%), categorized as good. Novelty/Originality of this study: The utilizing interactive tools such as Statcal, students can understand statistical concepts more deeply through a practical and contextual approach. This is relevant to be applied to statistics learning in schools and universities, especially in preparing students to face the challenges of the digital data era. In addition, this study also encourages teachers to integrate technology in learning to create a more engaging and effective learning experience.